Pengaruh Pelatihan Kerja, Kompetensi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Bank Jatim Kantor Cabang Syariah Kediri - Arrofi, Anik Qurniatin; Utami, Sasi; Laely, Nur; Marwanto, IGG Heru (Politeknik Raflesia Press, 2023)
The purpose of this study is to ascertain at Bank Jatim, Syariah Kediri Branch, the effects of job training, competency, and work discipline on employee performance. Following the scientific ideas of concreteness, objectivity, measurability, rationality, and systematicity, this study uses a quantitative research approach since the data consists of numbers and is investigated using statistical techniques. While the sample consists of a part of the employees—specifically, 75 individuals/respondents—the population considered in this study comprises 93 employees of Bank Jatim, Syariah Kediri Branch. Questionnaires, observations, and interviews constitute among the data gathering techniques. Validity and reliability tests, classical assumption tests, multiple linear regression tests, partial significance tests (t-test), simultaneous significance tests (f-test), and coefficient of determination comprise the data analysis techniques. The t-test value for job training of 2.947, which is higher than the t-table value of 1.66671, with a significance value of 0.004, shows that job training has an effect on employee performance. Consequently, it can be said that H1 is approved, so demonstrating the impact of work training on Bank Jatim, Syariah Kediri Branch, staff performance. The t-test result for competence of 2.554, which is higher than the t-table value of 1.66571, with a significant value of 0.013, shows how influence competence has on employee performance. Therefore, it can be said that H2 is acknowledged, thereby reflecting the impact of competency on Bank Jatim, Syariah Kediri Branch, staff performance. The t-test result for work discipline of 2.034, which is higher than the t-table value of 1.66571, with a significant value of 0.035, shows how influence of work discipline affects employee performance. Therefore, it can be said that H3 is approved, thereby demonstrating the effect of work discipline on Bank Jatim, Syariah Kediri Branch, employee performance.